THE PROBLEM OF FORMING AND DEVELOPING THE INFORMATION-COMMUNICATION COMPETENCE OF THE FUTURE PHYSICS TEACHER - Mirsaidova G.; Umirov Boboyor (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article talks about the content of educational work carried out during the organization of a folklore club and training, as well as the possibilities of learned songs for educating young people in the spirit of national values.